Efficacy of Oral Amoxilcillin in the Treatment of Non Community Acquire Pneumonia (Medical Forum Monthly, 2024)
Objectives: To assess the efficacy of oral Amoxicillin in the treatment of Non-severe community acquired pneumonia in children 2-59 months of age, attending the Pediatric Emergency Department LUMHS, Hyderabad.Study Design: Descriptive / Cross-Sectional Study.Place and Duration of Study: This study was conducted at the Department of Pediatric Emergency LUMHS, Hyderabad, from November 2015 to May 2016.Materials and Methods: A total of 80 children aged 2-59 months with signs of both fast breathing and chest in drawing were classified as pneumonia. Oxygen saturation and chest X ray were done in all cases. Treatment with Oral Amoxicillin 90mg/kg/day for 5 days was given and response to treatment was assessed on 3rd day of admission. Children who did not improve on 3rd day of admission were declared treatment failure and switched to 2nd line treatment.Results: In this study overall 78.7% children improved with Oral Amoxicillin 90mg/kg/day BD for 5 days, while 16.3% children had treatment failure on Oral Amoxicillin. Treatment failure was more commonly seen in children with oxygen saturation <95% on admission. 5% children defaulted due to parents concerns.Conclusion: Oral Amoxicillin is effective in 78.7 % children presenting with fast breathing and chest in drawing. Dissemination and Implementation of these findings will provide cost effective treatment and reduce burden on both government and private sector by reducing rates of admissions and prescription of costly antibiotics.